2019
DOI: 10.3389/fpls.2019.00968
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Genes Involved in the Biosynthesis of Caffeoylquinic Acids in Sunflower (Helianthus annuus L.)

Abstract: Sunflower ( Helianthus annuus L.) sprouts accumulate high amounts of caffeoylquinic acids (CQAs) including chlorogenic acid (5-CQA) and 1,5-diCQA. These compounds, which can be found in many plants, including tomato, globe artichoke, and chicory, have many health benefits, including antioxidant, antihepatotoxic, and antiglycative activities. However, CQA profiles and biosynthesis have not previously been studied in sunflower sprouts. In the present study, we found that 5-CQA and 1,5-diCQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…No putative signal peptides were found in the EpHTT or EpHQT sequences. Both EpHTT and EpHQT GFP-tagged proteins were cytosolically localized as reported for other HQTs 19 , 20 and showed highest activities at pH 7 (Fig. 2h and Supplementary Fig.…”
Section: Resultssupporting
confidence: 71%
“…No putative signal peptides were found in the EpHTT or EpHQT sequences. Both EpHTT and EpHQT GFP-tagged proteins were cytosolically localized as reported for other HQTs 19 , 20 and showed highest activities at pH 7 (Fig. 2h and Supplementary Fig.…”
Section: Resultssupporting
confidence: 71%
“…We investigated two well-characterized genotypes at two stages for their different CGA accumulation ( Fig 2A–2C ). Although a few genes involved in CGA biosynthesis had been reported in other plant species, such as tomato [ 21 , 22 ], Arabidopsis [ 23 , 24 ], Nicotiana tabacum [ 27 ], Lonicera japonica [ 50 , 51 ], Sunflower [ 52 ], Dandelions [ 53 , 54 ], Cecropia obtusifolia [ 55 ], the molecular mechanisms underlying in leafy sweet potato remains largely unknown. In the present study, a total of 29834 genes were identified based on the reference guided transcriptome analysis of two genotypes at two stages.…”
Section: Discussionmentioning
confidence: 99%
“…The specific primer sequences of sunflower genes, PAL1, C4H, CHS, CHI2, F3H, FLS1, DFR, F3 H, AN1, AN2, HCT, HQT, and C3H, were designed and are mentioned in Table 1, and the β-actin gene was used as an internal standard due to their stable expression in sunflower based on previous studies [19]. The qRT-PCR reaction was performed while using a CFX Connect TM Real Time System (BIO-RAD, Hercules, CA, USA).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…In sunflower, the phenolic compounds represent the most prominent bioactive compounds [19]. The polyphenol biosynthetic pathway can be divided into three sections: the main phenylpropanoid, flavonoid, and the chlorogenic acid biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%